SURVEI SARANA DAN PRASARANA OLAHRAGA DALAM PEMBELAJARAN PENDIDIKAN JASMANI DI SMPN 12 PALOPO - Rian, Rian; Ahmad, Ahmad; Taslim, Taslim; Hidayat, Rahmat (Jurnal Porkes, 2025)
This study aims to determine the availability of facilities and infrastructure at SMPN 12 Palopo school in physical education learning. This research used survey method. The population in the study was SMP Negeri 12 Palopo totaling 145 students. The sampling technique used purposive sampling. The data analysis technique in this study is to use descriptive analysis techniques. Data collection techniques using observation, documentation, research instruments. the results of research on facilities and infrastructure that support the physical education learning process of students of SMP Negeri 12 Palopo are 39.55% in the category of less to support the physical education learning process in accordance with the applicable curriculum. This finding indicates that the existing facilities at SMP Negeri 12 Palopo are far from adequate and require serious attention for improvement. The limitations of physical education facilities and infrastructure at SMP Negeri 12 Palopo are caused by the limited ability of schools to procure these facilities. In conclusion, the facilities at SMP Negeri 12 Palopo are far from adequate and require serious attention for improvement. The limitations of physical education facilities and infrastructure are caused by the limited ability of schools to procure these facilities.